2012
DOI: 10.1007/s12070-012-0545-2
|View full text |Cite
|
Sign up to set email alerts
|

A Questionnaire-Based Survey of Indian ENT Surgeons to Estimate Clinic Prevalence of Acute Otitis Media, Diagnostic Practices, and Management Strategies

Abstract: Acute otitis media (AOM) is common in Indian children, but there is limited published information on its clinic prevalence, clinicians' diagnostic practices, and their management strategies. We approached 649 ear-nose-throat (ENT) surgeons to assess these aspects of AOM. We conducted the survey between May 2010 and February 2011 with the same set of ENT surgeons practising across India, once each during summer, monsoon and winter, using a validated 36-item questionnaire to record their reflective recall. 78 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In PCV-unimmunised Chinese children with pneumococcal AOM, a significant proportion of clones were also resistant to antibiotics 28. In India, otolaryngologists reported that they treated 98% of AOM episodes with antibiotics, and amoxicillin/clavulanic acid was the first-line therapy 29. We acknowledge limitations in our study: (1) we focused on only 12 guidelines.…”
Section: Discussionmentioning
confidence: 98%
“…In PCV-unimmunised Chinese children with pneumococcal AOM, a significant proportion of clones were also resistant to antibiotics 28. In India, otolaryngologists reported that they treated 98% of AOM episodes with antibiotics, and amoxicillin/clavulanic acid was the first-line therapy 29. We acknowledge limitations in our study: (1) we focused on only 12 guidelines.…”
Section: Discussionmentioning
confidence: 98%
“…There is wide variation noted in the prevalence of AOM worldwide and particularly from India. While the prevalence worldwide has been reported to be around 10.8%, in India it has been reported to be between 4 and 43% based on a questionnaire and otoscopic assessment ( Ren et al., 2018 ; Monasta et al., 2012 ; DeAntonio et al., 2016 ; D’silva et al., 2013 ; Gaur et al., 2009 ; Sophia et al., 2010 ). This variation could be because of different ways of reporting AOM ( Sophia et al., 2010 ; Srikanth et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%